ANALYSIS OF COMMUNICATION ETHICS FOR GENERATION Z IN PATUMBAK DISTRICT, DELI SERDANG REGENCY - Monica Nur Annisa; Erwan Effendi (Journal Analytica Islamica, 2025)
This study aims to analyze the communication ethics of Generation Z in Patumbak District, Deli Serdang Regency, both in direct and digital communication, especially social media, with an approach of ethical values in Islam. Generation Z is known as digital natives who are very close to information technology, but this closeness also influences communication patterns and the application of ethical values. The study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation, and triangulation of sources is carried out to test the validity of the data. The results of the study indicate a shift in the communication ethics of Generation Z, both in face-to-face interactions that tend to decrease in terms of politeness, empathy, and emotional involvement, as well as in digital communication that is vulnerable to free expression without ethical considerations. In the Islamic context, the principles of qaulan are an important reference in forming polite and civilized communication. Therefore, an understanding of communication ethics based on moral and religious values needs to be strengthened to maintain the quality of communication of Generation Z in the digital era.